Comparison of the Functional Outcome Between Titanium and Stainless Steel Interlocking Nails in Tibial Shaft Fracture Treatment - Khan, Abdul Mannan; Shami, Ali Miraj (Biological and Clinical Sciences Research Journal, 2025)
The treatment of tibial shaft fractures remains a challenging issue in orthopedic practice. The choice of interlocking nail material, whether titanium or stainless steel, plays a crucial role in functional recovery and complication rates. This study aimed to compare the functional outcomes of treating tibial shaft fractures with titanium versus stainless steel interlocking nails. Methods: A prospective cohort study was conducted with 160 patients who underwent tibial shaft fracture fixation using either titanium (Group A) or stainless steel (Group B) interlocking nails. Functional outcomes were evaluated based on the percentage of excellent, good, fair, and poor outcomes. Additionally, factors such as age, gender, duration of fracture, anatomical side of the fracture, and trauma mechanism were analyzed for their impact on functional outcomes. Statistical significance was set at p < 0.05. Results: The titanium group exhibited superior outcomes, with 72.50% of patients achieving excellent results compared to 58.75% in the stainless steel group. Poor outcomes were significantly lower in the titanium group (5.00%) compared to the stainless steel group (15.00%). Stratification by age, gender, and trauma mechanism revealed that males and patients with fractures treated within 5 days had the best outcomes. Road traffic accidents were linked to poorer recovery outcomes. Conclusion: Titanium interlocking nails resulted in better functional outcomes compared to stainless steel nails in the treatment of tibial shaft fractures. This study suggests that titanium may offer superior performance, with fewer complications and better recovery rates. Further studies are needed to confirm these findings and explore the long-term benefits of titanium nails in fracture healing.